Real-Time 14-Gbps Physical Random Bit Generator Based on Time-Interleaved Sampling of Broadband White Chaos - Longsheng Wang; Tong Zhao; Daming Wang; Danyu Wu; Lei Zhou; Jin Wu; Xinyu Liu; Yuncai Wang; Anbang Wang (IEEE Photonics Journal, 2017)
We experimentally demonstrate a real-time high-speed physical random bit generator using the time-interleaved sampling of broadband white chaos. The white chaos is generated by optical heterodyning of two external-cavity feedback laser diodes. It has a white-noise-like spectrum with a 3-dB bandwidth of 16.7 GHz and a symmetric amplitude distribution and has no time-delay signatures of the external feedback cavities. An analog-to-digital converter (ADC) chip integrated by two time-interleaved sub-ADCs with a maximum sampling rate of 7 GHz is utilized to discretize the white chaos into parallel binary streams. After real-time interleaving combination and exclusive-OR operation in the field-programmable gate array (FPGA), a 14-Gbps binary stream with verified randomness is achieved.